The description of mate choice - Edward, D. A. (Behavioral ecology, 2015)
Mate choice is an important evolutionary process influencing a vast array of traits and ecological processes. Although the study of mate choice has proved to be hugely popular, the number of ways in which mate choice can be described is complex and a bewildering array of terminology has developed. The author begins by summarizing some examples of the range of terms used to describe choice that expose this complexity. The author then shows how the information conveyed by different mate choice descriptors can be better understood by comparison to null expectations, that is, the expected variation in a trait when mate choice is not expressed. This comparison is important because many traits that might be affected by mate choice, such as mating rate, mate search effort, and responsiveness, also vary in non-choosy individuals. This is in contrast to other traits, such as the slope of a preference function and mate assessment effort, for which null expectations are predictable. By understanding the null expectation for a trait, its utility as a descriptor of mate choice can be gauged. From this basis, the author suggests an alternative approach to the description of mate choice based upon a principle of describing variation in both "what" is preferred and "by how much" it is preferred. Crucially, the author describes how this approach might apply to a wide range of preference function shapes, thus aiding comparisons across taxa. Finally, the author considers how an improved appreciation of the way mate choice is described can inform future research.Lay Summary Mate choice is an important evolutionary process and a popular subject, yet it has become associated with a bewildering array of jargon. Opportunities for future research to help us understand mate choice can be guided through an improved appreciation of this language. To steer a more concise and accurate approach, I summarise ways in which mate choice is described and discuss merits of the various characters that can be used to describe choice.